PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MEDIA TEKA TEKI SILANG DI KELAS IV SEKOLAH DASAR - Sari, Maharani Purnama; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the improvement of integrated thematic learning outcomes using crossword media in class IV of SDN 19 ATTS, Bukittinggi . The type of this research is Classroom Action Research (PTK). The results of research showed the increasing on: a) the score oh the lesson plan in cycle I was 90% (B), cycle II 97,5% (SB); b) aspect observation of teacher cycle I 87.3% (B), cycle II 97% (SB); c) aspects observation of student cycle I students 81,25% (B) and the second cycle II 94% (SB); d) lthe aerage f cycle 1 was I 72,75; and the second cycle II was 81,6. Based on these data it can be conclude that using crossword media can improve student learning outcames in integrated thematic learning.